ANALISIS PENERAPAN BALANCED SCORECARD SEBAGAI ALAT PENGUKURAN KINERJA (Studi Kasus: di BPRS Artha Surya Barokah Semarang) - Ayuningtyas Adiputri; Fatmasari Sukesti (Universitas Muhammadiyah Semarang, 2013)
The economic crisis a few years ago to make economic conditions in Indonesia have made great progress , so that requires leaders and company management to improve competitiveness by providing the best services for its customers in order to survive . One of the company's goal is to support their survival to earn profits . The company's main goal can be achieved if the maximum performance of the company and work well , because of the success and the success of an enterprise is the ability to generate profit and expand its business .The population in this study were clients and employees of PT . Surya Artha SRB Barokah Semarang . number of employees required sample is 45 people and the customer sample 99.88 or 100 people . The analytical method used is descriptive analysis .Results of the study is a financial ratio used is ROA , ROA and LDR . Results of this study indicate that the SRB Surya Artha Barokah Semarang from 2010 through 2012 can achieve cost effectiveness and generate optimal profits . Performance of the financial perspective shows good results even continue experiencing good growth . Results of this study indicate that explains that the market share in Semarang Barokah Surya Artha SRB increased to reach an average value of 161.88 % . Surya Artha SRB Barokah Semarang maintain competitiveness , interest rates , increasing mastery of market segments in order to meet customer needs . Surya Artha SRB Barokah Semarang start expanding operations by expanding the branch network , the development of a variety of products and services offered . It aims to improve after-sales service and provide additional benefits to our customers in order to still have the loyalty of the BPRS Artha Barokah Surya Semarang . Results of measurements describing the success ratio AETR increased efficiency , effectiveness and accuracy of the transactions conducted BPRS Artha Barokah Surya Semarang . Results of this study showed improvement indicated that employee productivity is increasing every year . This happens because in assessing the percentage of successful employee training SRB Surya Artha Barokah Semarang . Regarding the level of employee satisfaction shows the value of the overall average score of 4.03 . The figure shows the results of a good or satisfied . Keywords : financial perspective , customer perspective, internal business processes , learning and growt perspective